EMSys an emotion monitoring system for call center agents - Boco, Princess Florianne O.
Emotion monitoring system for call center agents is a prosody-based emotion monitoring system for call center environments. It simplifies the tracking and management of emotion extracted from call center agent-client conversations. The system is composed of four modules: Emotion Detection, Emotion Analysis and Report Generation, Database Manager, and User Interface. The Emotion Detection module uses Digital Signal Processing algorithms to extract the low-level features necessary for reliable emotion detection. Utterance detection will first process the speech signals, then the features will be extracted, afterwards, the Support Vector Machines (SVM) classifier will detect the emotions contained in an utterance. The four emotions being detected by the system are hapiness, anger, boredom and neutral. The Emotion Analysis and Report Generation module performs computational analysis of the detected emotions during conversations. This module is also responsible for polishing the output of Emotion Detection module to provide a more presentable output of sequence of emotions of the agent and the caller. The Database Manager is the one responsible for the management of the database wherein it handles the creation, deletion and update of data. The Interface module serves as the view and user interface for the whole system. The system is comprised of a stand alone application and a web based application. The stand alone application displays the detected previous and current emotions of both the agent and the caller. On the other hand, the web based application provides the supervisor reports and analysis of the emotions expressed by the agents during conversations. Using the Model View Controller (MVC) approach, the emotion monitoring system is scalable, reusable and modular.